On Hopf algebras with triangular decomposition - Vay, Cristian Damian (2019)
In this survey, we first review some known results on the representationtheory of algebras with triangular decomposition, including the classification of the simple modules. We then discuss a recipe to construct Hopf algebras with triangular decomposition. Finally, we extend to these Hopf algebras the main results of a previous work of the author regarding projective modules over Drinfeld doubles of bosonizations of Nichols algebras and groups.